THE FORMAL SECTOR LABOR PERFORMANCE UNDER THE SHADOW OF JOB AUTOMATION - Andriyanty, Reny; Bachri, Syamsul; Rambe, Delila; Majid, Abdul Halim Abdul (Universitas Brawijaya, Indonesia, 2023)
Data on formal sector employment in DKI Jakarta shows a significant and negative relationship between investment and employment. Now, industries are more capital-intensive and prefer to implement automation, IoT robotics, and artificial intelligence. The purpose of this study was to build a model of the relationship between character, work ability, organizational commitment, and organizational culture as they relate to the performance of formal sector employees. The research method was descriptive quantitative. The sampling technique was non-probability sampling. Samples were determined by accidental sampling and were collected from 151 respondents who were formal sector employees of DKI Jakarta. Structural Equation Model applied in data processing. The results of the research indicated that Character factor and workability have a significant direct influence on employee performance on formal sector employees in DKI Jakarta. Only the organizational commitment factor is not significantly correlated directly to performance. Indirect relationship analysis states that organizational culture through organizational commitment correlates with character and workability factors which ultimately have an impact on performance. The implication of this research shows that the creativity factor and environmentally friendly work behavior need to be improved by employees.